Implementation of Pushing Reminder Technique for Women During The First Stage of Labor and Perineal Rupture Events - Ratnasari, Febi; Imanuddin, Bayu; Febriyani, Fitria (IJNP (Indonesian Journal of Nursing Practices), 2020)
Background: Rupture of the birth canal or perineal tear cannot be considered a minor injury because it contributes to maternal morbidity and mortality. The perineal rupture causes pain and can increase until the seventh day. Perineal rupture also causes 4-5% of mortality in postpartum mothers.Objective: The purpose of this study is to find out the effect of pushing reminder technique implementation on women during the first stage of labor and perineal rupture event.Method: The research method used was pre-experimental with intact group comparison design (post-test only control with 15 control respondents and 15 intervention respondents).Results: The results showed that the average age of the respondents was 26 years old with status as a housewives (93.3%), and the majority of the educational background was high school graduate (86%). By using the Mann-Whitney test, the results of alpha is 0.05 (0.369), so there is no relationship between the reminder of pushing technique and the occurrence of perineal rupture.Conclusion: There are other factors that affected the tears of the perineum such as baby’s weight, previous history of perineal rupture, the rigidity of perineal muscles and lack of skills of health care providers to hold the perineum at the moment of baby’s head expulsion, this indicated that is no relationship between the reminder of pushing technique and the occurrence of perineal rupture.Recommendation: It is adviced for Public Health Care Center is to provide educational media containing information for pregnant woman in a form of electronic media in the waiting room and through education of pregnant women regarding labor and perineum tear so that pregnant women understand the causes of perineal tear.